Adapting to Climate Change : Assessing World Bank Group Experience--Phase III of the World Bank Group and Climate Change - Independent Evaluation Group (World Bank, Washington, DC, 2015)
This paper constitutes the third and final volume of a series of assessments of the World Bank Group's engagement with climate change issues. The first focused on World Bank involvement in policy issues related to greenhouse gas mitigation. It was mainly concerned with the potential for energy price reform and energy efficiency policies to yield dividends in growth, fiscal savings, and climate change mitigation. The second volume examined project-level lessons related to greenhouse gas mitigation. This volume draws lessons from World Bank and International Finance Corporation (IFC) engagement in climate change adaptation. Like its predecessors, but to an even greater extent, this evaluation has a strong focus on learning, as the Bank Group explores a newly defined agenda. Climate change adaptation has only recently captured widespread policy attention. In strong contrast to climate mitigation, whose progress can be tracked along a single global metric (the atmospheric concentration of greenhouse gases), adaptation takes many forms, is intensely local, and resists easy definition and measurement. To a much greater extent even than climate change mitigation, adaptation is intertwined with development. Thus this evaluation looks not only at activities explicitly labeled 'climate adaptation' but also at a selection of those that might be expected to be adaptive, even if not so labeled.